COMPARISON OF THE QUALITY OF THE MINISTRY OF COMMUNICATION AND INFORMATICS WEBSITE USING WEBQUAL 4.0 METHOD AMONG NON-IT BACKGROUND LAYPERSONS' PERCEPTIONS - Alexander; Weihuan Zhou (Bulletin of Engineering Science, Technology and Industry, 2023)
The assessment results reveal interesting insights into the perception of the Kominfo website's quality in Lhokseumawe City. The analysis highlights two distinct groups: the IT professionals and the general public/non-IT users. The IT professionals, comprising 20 respondents, gave positive evaluations, with an average EC score above 3, indicating that their expectations were largely met by the website. However, there were a few users who provided lower ratings, particularly in terms of mobile accessibility (QA16), indicating some difficulty in accessing the website via mobile devices. On the other hand, the general public/non-IT users from Lhokseumawe City, consisting of 45 respondents, exhibited a mixed perception. They recorded an average EC score of 7.652, showcasing a higher level of satisfaction with their expectations being met. Nonetheless, the average D score of 1.852 indicated a significant mismatch between their expectations and the website's actual performance. Despite this discrepancy, the overall website quality (OWQ) received a positive average score of 4.752, reflecting their relatively positive assessment of the website's overall quality. However, it is essential to consider the importance weight (IW) assigned by this group, with an average score of 1.59. This suggests that they gave relatively lower importance to some questions in the assessment. As such, certain aspects may require improvement to align better with their expectations. Overall, the results underscore the need for further enhancements to specific areas of the website, especially in terms of mobile accessibility, content comprehension, and addressing the mismatch between user expectations and actual performance. By addressing these aspects, the website can improve its overall quality and better cater to the diverse needs and preferences of both IT professionals and the general public/non-IT users in Lhokseumawe City.